OF VALERIAN POETRY AND TANPINAR - Yener, Melih (İshak KÜÇÜKYILDIZ, 2023)
“Valerian poetry” is a term used to describe the poetic understanding of the French poet Paul Valéry and the poems written in accordance with this understanding. Valéry’s art is based on the desire and ideal of harmony. He accepts poetry as an art of harmony like music and architecture. He gives importance to the sound colors and musical identities as much as the meanings of the words. According to him, the poet is a word jeweler. Poetry is an art that can mirror the most complex layers and tides of the human soul, and even if it is not, it is an art that will adopt it as an ideal. It should evoke a prayer and some sort of magic effect on the person. This does’nt happen with the usual and every day use of words. It happens with the realization that words are not just a messenger of meaning, but that there is a deep harmony in them that is “seen with the ear”, “heard with the eye” and achieved as a result of the natural development of the language over the centuries. According to Valéry, language is both a poet’s greatest ordeal and his greatest blessing.He believes that classical values, which were liquidated by the pressure of industrialization, wars covering the earth and consumer culture, should be preserved in art. He always aims for the best in poetry. However, he thinks that the most perfect is also something unattainable. With these views on language and harmony and the poems he wrote within this framework, Paul Valéry should be seen as a poet who performs his art within the discipline of poésie pure = pure poetry, theorized by Henri Brémond. Valéry has more or less influenced the poets who can be seen and evaluated in the pure poetry valley in Turkish poetry. However, the poet Ahmet Hamdi Tanpınar, whom he influenced most clearly in Turkish poetry. This article gives information about Paul Valéry’s art and examines his influences on Tanpınar’s understanding of poetry. The concluding part of the article reveals the author’s thoughts on Valerian poetry.

“Valeryen şiir” Fransız şair Paul Valéry’ nin şiir anlayışını ve bu anlayışa uygun yazılan şiirleri nitelendirmek için kullanılan bir tabirdir. Valéry’ nin sanatı ahenk arzusu ve ideali üzerine kuruludur. O, şiiri musiki ve mimari gibi bir armoni sanatı olarak kabul eder. Kelimelerin anlamları kadar ses renklerine ve müzikal değerlerine de ehemmiyet verir. Şair ona göre bir kelime kuyumcusudur. Şiir insan ruhunun en karmaşık tabakalarına ve gelgitlerine ayna olabilecek, olamasa bile bunu ülkü edinecek bir sanattır. Ona göre şiir kişide bir dua ve bir tür sihir etkisi uyandırmalıdır. Bu ise kelimelerin her zamanki ve her ağızdaki kullanılışıyla olmaz. Kelimelerin bir anlam tebliğcisinden ibaret olmadığının, onlarda “kulakla görülen”, “gözle işitilen” ve dilin yüzyıllar süren doğal gelişimi neticesinde erişilen derûni bir ahenk bulunduğunun idrakiyle olur. Valéry’ ye göre dil bir şairin hem en büyük çilesi hem de en büyük nimetidir. Paul Valéry, endüstrileşmenin, yeryüzünü kaplayan savaşların ve tüketim kültürünün tazyikiyle sırt çevrilen klasik değerlerin sanatta muhafazasından yanadır. O şiirde daima en mükemmeli gaye edinir. Ancak en mükemmelin de ulaşılamaz bir şey olduğunu düşünür. Dil ve ahenk meselelerindeki bu görüşleri ve bu çerçeve içinde yazdığı şiirlerle Paul Valéry sanatını, Henri Brémond tarafından kuramsallaştırılan poésie pure=saf şiir disiplini içinde icra eden bir şair olarak görülür. Türk şiirinde öz şiir vadisi içinde görülüp değerlendirilebilecek şairleri Valéry az veya çok etkilemiştir. Ancak onun Türk şiirinde en bariz şekilde etkilediği şair Ahmet Hamdi Tanpınar’dır. Bu makale Paul Valéry’ nin sanatı hakkında bilgi vermekte ve onun Tanpınar’ın şiir anlayışı üzerindeki etkilerini incelemektedir. Makalenin sonuç kısmı, yazarın Valeryen şiir hakkındaki düşüncelerini ortaya koymaktadır.
VALERYEN ŞİİR VE TANPINAR